Influence of experiencing SARS-CoV-2 infection on anxiety levels in Chinese patients undergoing third molar surgery - Zhu, Junfei; Li, Wenjing; Wei, Fang; Zhang, Dan; Wang, Meng; Zhang, Huiyun; Zhang, Ye (Frontiers in Psychology, 2024)
Background In China, most of the citizens experienced SARS-CoV-2 infection since the end of 2022. The Coronavirus disease 2019 (COVID-19) pandemic affected people’s physical health and also had a significant impact on mental well-being. The present study aims to discover if the experience of SARS-CoV-2 infection influences patients’ anxiety toward third molar surgery in the Chinese population. Materials and methods The present study took the form of a questionnaire survey. From January 1, 2023, to June 30, 2023, patients who went to the Stomatology Center of China-Japan Friendship Hospital (Beijing, China) for the third molar extraction were included according to the inclusion criteria. The information on COVID-19 infection and the Modified Dental Anxiety Scale (MDAS) was collected. The software SPSS 22.0 was used for the statistical analyses. Results A total of 574 survey results were harvested in the present study. The infection rate of COVID-19 was 86.6% (p > 0.05). The Average MDAS scores between patients who had been infected with COVID-19 and patients who were never infected were not significantly different (11.65 ± 4.41 vs. 11.42 ± 4.41, p > 0.05). The subgroup analysis was conducted according to the length of time after the recovery of COVID-19 (Model 1), and the highest temperature during the infection (Model 2). In Model 1 and Model 2, the one-way ANOVA test did not find statistical significance between the groups (Model 1 p = 0.114; Model 2 p = 0.481). The MDAS scores in female patients were significantly higher than in male patients (12.29 ± 4.53 vs. 9.91 ± 3.80, p < 0.001). Patients who extracted double teeth got significantly higher MDAS scores than those who extracted single teeth before the surgery (12.03 ± 4.74 vs. 11.24 ± 4.18, p = 0.037). Conclusion The present study did not establish a significant impact of SARS-CoV-2 infection on the anxiety levels associated with third molar surgery among Chinese patients. The potential long-term biopsychological effects of the virus warrant further investigation.